2022
DOI: 10.1007/s00705-022-05516-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes to virus taxonomy ratified by the International Committee on Taxonomy of Viruses (2022)

Abstract: This article reports the changes to virus taxonomy approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in March 2022. The entire ICTV was invited to vote on 174 taxonomic proposals approved by the ICTV Executive Committee at its annual meeting in July 2021. All proposals were ratified by an absolute majority of the ICTV members. Of note, the Study Groups have started to implement the new rule for uniform virus species naming that became effective in 2021 and mandates the binomial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
162
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(164 citation statements)
references
References 5 publications
1
162
0
1
Order By: Relevance
“…In conclusion, this study describes the discovery of a novel anellovirus species which represents the rst complete genome within the genus Mutorquevirus. Comparative genomic analysis showed that TTEqV2 shares many conserved features with previously reported TTVs and it has been recognized as a novel species by the ICTV 13 . This, along with previous studies using similar methods [15][16][17][18] demonstrates the power of HTS for characterization of unexpected and/or novel viruses in a variety of hosts and sample types .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In conclusion, this study describes the discovery of a novel anellovirus species which represents the rst complete genome within the genus Mutorquevirus. Comparative genomic analysis showed that TTEqV2 shares many conserved features with previously reported TTVs and it has been recognized as a novel species by the ICTV 13 . This, along with previous studies using similar methods [15][16][17][18] demonstrates the power of HTS for characterization of unexpected and/or novel viruses in a variety of hosts and sample types .…”
Section: Discussionmentioning
confidence: 75%
“…Here, we report the complete genome sequence of a novel TTV species, Torque teno equus virus 2 (TTEqV2) isolate Alberta/2018, discovered via high throughput sequencing (HTS) of tissue samples collected from a horse that died of nonsuppurative encephalitis. The novel virus described here has been o cially approved by the ICTV as a novel species within the genus Mutorquevirus 13 . The name of the novel virus complies with current ICTV naming guidelines, however switching to a binomial naming system has been suggested by the ICTV but not yet formally adopted 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Equine influenza (EI) is an acute, contagious infectious disease of horses, donkeys, and other members of the family Equidae caused by the equine influenza A virus of the genus Orthomyxovirus within the Family Orthomyxoviridae [ 1 ]. The characteristic clinical signs of influenza virus infection in equines include high fever, cough, and serous nasal discharge, and abortion may occur in pregnant animals.…”
Section: Introductionmentioning
confidence: 99%
“…However, phylogenesis analysis of the nearly complete or entire genome has revealed discoveries of porcine parvovirus in the form of PPV2 to PP7. PPV1 is classified as a protoparvovirus belonging to the subfamily Parvovirinae, family Parvoviridae (Cotmore et al, 2019;Walker et al, 2020). The viral genome consists of two main open frames (ORFs), ORFs1 and ORFs2.…”
Section: Introductionmentioning
confidence: 99%